Development of Jaw Script Recognition Media Through Card Media Using Augmented Reality For Elementary School Children - Baihaqi, Bagus Hirnov; Aristyagama, Yusfia Hafid; Maryono, Dwi (Journal of Global Hospitality and Tourism Technology, 2024)
This research aims to develop and determine the feasibility of android learning media on the subject of Javanese script using augmented reality and card games for elementary school children. This research was conducted because of the lack of interest of students in learning Javanese script which is considered difficult and unimportant because it is less useful in terms of its usefulness in life practice and keeping Javanese script sustainable. The study used the ADDIE model with feasibility test stages using TAM. The result of the development of learning media is the creation of the "NGAKSARA" application as well as the "KARA" card media which can help students in introducing Javanese script. At the feasibility test stage, it was found that the learning media "NGAKSARA" is suitable for use in teaching and learning activities.